Association of a 62 Variants Type 2 Diabetes Genetic Risk Score With Markers of Subclinical Atherosclerosis: A Transethnic, Multicenter Study. (June 2015) - Dauriz, Marco; Porneala, Bianca C.; Guo, Xiuqing; Bielak, Lawrence F.; Peyser, Patricia A.; Durant, Nefertiti H.; Carnethon, Mercedes R.; Bonadonna, Riccardo C.; Bonora, Enzo; Bowden, Donald W.; Florez, Jose C.; Fornage, Myriam; et al.
Abstract : Background—: Type 2 diabetes mellitus (T2D) and cardiovascular disease share risk factors and subclinical atherosclerosis (SCA) predicts events in those with and without diabetes mellitus. T2D genetic risk may predict both T2D and SCA. We hypothesized that greater T2D genetic risk is associated with higher extent of SCA. Methods and Results—: In a cross-sectional analysis, including ⩽9210 European Americans, 3773 African Americans, 1446 Hispanic Americans, and 773 Chinese Americans without known cardiovascular disease and enrolled in the Framingham Heart Study, Coronary Artery Risk Development in Young Adults, Multi-Ethnic Study of Atherosclerosis, and Genetic Epidemiology Network of Arteriopathy studies, we tested a 62 T2D-loci genetic risk score for association with measures of SCA, including coronary artery or abdominal aortic calcium score, common and internal carotid artery intima-media thickness, and ankle-brachial index. We used ancestry-stratified linear regression models, with random effects accounting for family relatedness when appropriate, applying a genetic-only (adjusted for sex) and a full SCA risk factors–adjusted model (significance, P <0.01=0.05/5, number of traits analyzed). An inverse association with coronary artery calcium score in Multi-Ethnic Study of Atherosclerosis Europeans (fully-adjusted P =0.004) and with common carotid artery intima-media thickness in the Framingham Heart Study ( P =0.009) was not confirmed in other study cohorts, either separately or in meta-analysis. Secondary analyses showed no consistent associations with β-cell and insulin resistance genetic risk sub-scores in the Framingham Heart Study and in the Coronary Artery Risk Development in Young Adults. Conclusions—: SCA does not have a major genetic component linked to a burden of 62 T2D loci identified by large genome-wide association studies. A shared T2D-SCA genetic basis, if any, might become apparent from better functional information about both T2D and cardiovascular disease risk loci. Abstract : Supplemental Digital Content is available in the text.